Elicitation of Preferences for Improvements in Ostomy Pouches – A Discrete Choice Experiment - Ole Bonnichsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2010)
This paper attempts to examine and measure ostomates' preferences for improvements in ostomy pouches. Described are the study design, elicitation procedure and resulting preference structure of the Swedish ostomate sample. The method used to elicit the preferences is a Discrete Choice Experiment (DCE), where respondents are asked to choose between alternatives in choice sets. Each alternative is comprised of a number of attributes relating to the adhesive, filter and flexibility of ostomy pouches. The choice between alternatives made by the respondent implies an implicit trade-off between the attributes and allows for the estimation of individuals' Willingness to Pay (WTP) for the attributes of ostomy pouches when cost is included as an attribute. The data consists of 254 ostomates responding to the survey. The respondents have positive WTP for all improvement attributes presented to them in the survey, with strongest preferences for reducing the number of leakages. The DCE utilised in the survey performs well in terms of reliability and validity of the obtained results. The results suggest that since reducing leakages is the most important attribute for the respondents when making their choices, emphasis should be placed on this attribute when decisions are made as to the allocation of scarce health care resources within research and development aimed at improving ostomy pouches.
Keywords: 330; Discrete Choice Experiment; stated preferences; WTP